Notes of Protection: A Comparative Analysis of Music Copyright Laws and Enforcement - Siregar, Runi Hilda Fadlani (Universitas Muhammadiyah Yogyakarta, 2023)
Music copyrights are not only considered as commodities but also considered as private property which must be recognized and protected by the state. In Indonesia, legal protection for copyright holders and creators is conducted through the National Collective Management Organization, while in Malaysia those issues are handled by Music Rights Malaysia Berhad. The purpose of this research using a comparative legal concept approach is to provide information about music copyright protection in Indonesia and Malaysia regarding legal issues regarding the position of the music copyright protection agency as well as prosecution and legal remedies for copyright infringements within the country and across countries. This study used normative juridical legal research. The results of study show that National Collective Management Institute (NCMI) and Music Rights Malaysia Berhad (MRM) have the same characteristics, namely as independent institutions and have attributive authority to take legal action against Music copyright violations. Furthermore, MRM has a narrower range of royalty collection than NCMI. In addition, MRM has no obligation to mediate if the case is a civil case. Besides, legal efforts that can be carried out by NCMI and MRM can be through the realm of criminal or casuistry litigation or arbitration.